Analisis Pemilihan Siswa Untuk Jalur SNMPTN dengan Metode Weighted Product (WP) Dan Weighted Sum Model (WSM) - Tuslaela, T; Nazarius, Jerry Kristian (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2021)
SNMPTN (State Higher Education Entrance National Selection) is one of the pathways to be able to enter State Universities, this can be proven by the number of students who are interested in being able to enter State Universities with this pathway. SMAN 2 Depok directs their students so that they are not wrong in choosing the chosen State University. But there are still many students who are still doubtful about which university they will choose according to their abilities. With this problem many students end up choosing universities that are not within their abilities. Therefore, by using a Decision Support System which makes decisions based on data held by students can help determine the best university for students. The method used is Weighted Product (WP) and Weighted Sum Model (WSM), the criteria used for this method use the results of semester 1 to 5 grades that have been achieved by students. Using these 2 methods will produce different values for each university and each method will produce different grades. With this, students of SMAN 2 Depok can consider which university they will choose.